Economic effects of ambient air pollution on consumer shopping behaviors - Jung, Hojin (Economics and Business Letters, 2020)
In this paper, we address why the lack of research on the indirect economic effect of air pollution arises and explored the desirable features of data that allow such examination. In light of scanner panel data on individual transactions from a region with significant fluctuations in the level of particulate matters, our empirical investigation reveals that the economic effect of air pollution is statistically and economically significant through the disruption on consumption behaviors. Our discussion on the essential features of the data for the systematic analysis on the economic effect of air pollution and empirical evidence based on such data provides ample guidance for the future research.